Effect of Chlorhexidine and Orthodentol Mouthwash on Oral Hygiene of Patients Who Underwent Mechanical Ventilation, Hospitalized in Intensive Care Unit - Hojjat Mirzakhani; Haydeh Heidari; Ali Hasanpour; Fatemeh Deris (Iran University of Medical Sciences, 2017)
Background: Providing oral hygiene in patients with a tracheal tube in the mouth is one of the most important tasks of nurses. This study has been conducted with the aim of comparing the effects of two mouthwash solutions (chlorhexidine and orthodentol) on the oral hygiene of patients with respiratory ventilation device and hospitalized in intensive care units. Methods: This is a clinical trial in which 90 patients with oral tracheal tube entered the study through simple sampling method. Inclusion criteria were being insensitive to herbal compounds and aged 15-85 years. They were divided randomly into two intervention (orthodentol) and control (chlorhexidine) groups. Each group had 45 subjects. The Beck Oral Hygiene Checklist was used to collect data (before and after intervention). Data were analyzed using SPSS software. Results: Patients in intervention and control groups were similar in terms of demographic characteristics, oral hygiene, and other characteristics. Oral hygiene in patients in both orthodentol and chlorhexidine groups had a significant improvement after intervention. Conclusion: The comparison of orthodentol and chlorhexidine oral mucosal effects showed that oral hygiene of patients hospitalized in intensive care units was improved to a certain extent. Considering the benefits of herbal compounds, orthodentol mouthwash can be mentioned as an appropriate alternative for chlorhexidine.